Rethoric in Radio Advertisements’ Discourse - Abu Bakar, Siti Saniah (2008)
Rhetoric, that is the art of using beautiful and attractive language to inform, persuade and influence the readers’ or listeners’ minds plays an important role in advertisements. The advertising sector that is rapidly developing today, contributing towards the country’s economic growth relies on rhetoric to achieve its advertising aims. With the aim of selling their products or informing the public, advertising through the media, depends heavily on the effectiveness of the language being used. As a media channel, radio which has the characteristics of a good advertising channel and efficient broadcast with a lower coast as compared to other media is the choice for this research. As such, advertisements aired by the most popular and the highest revenue generating radio station in Malaysia, Era.FM is selected as the subject for the case study subject to identify, analyse and explain the words and phrases that have become the elements of rhetoric that used by advertisers on air. Using audio recording technique, advertisements were recorded for a period of 3 months for texts analysis based on the Interpersonal Rhetoric approach forwarded by Leech (1993). The research and study proves that the approach can be used to analyse the rhetoric in radio advertisements’ discourse. Outcome of the research shows that radio advertisement in Malay language has developed a strong base in constructing its rhetoric without neglecting the politeness and culture in Malay customs. This research has clearly proven the strength of the Malay language in playing its role in generating the national economy through advertising. Through such a research, it is hoped that knowledge in the field of rhetoric, especially radio advertising rhetoric will become stronger, more establish, valuable and will be able to provide a larger contribution to the community and the country.